Motivasi Belajar Bahasa Inggris sebagai Alat Komunikasi Profesional bagi Mahasiswa S1 Farmasi Klinik dan Komunitas: Motivation to Learn English as a Professional Communication Tool for Undergraduate Students of Clinical and Community Pharmacy - Dewi, Kadek Maya Cyntia; Suryati, Ni Wayan Novi; Rusanti, Putu; Wismadewi, I Gusti Agung Galuh (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
In the era of globalization, English has become the dominant international language in various fields, including health and pharmacy. Students’ motivation to learn English often varies, depending on academic needs, career prospects, personal experiences, and their learning environment. Therefore, it is essential to understand in depth the motivation of Clinical and Community Pharmacy undergraduate students to learn English as a professional communication tool. This study aims to analyze various aspects of English learning motivation among Clinical and Community Pharmacy undergraduate students. By understanding the factors that encourage or inhibit their motivation, it is hoped that more effective and relevant learning strategies can be designed to support the development of their English language competence in academic and professional contexts. The research method used is a combination of quantitative and qualitative. Quantitative data were obtained through questionnaires distributed to 30 students, while qualitative data were obtained from semi-structured interviews with 10 students. The results showed that students’ intrinsic motivation had an average score of 4.2, while extrinsic motivation reached 3.8. Career relevance was the most motivating factor, with a score of 4.5. Qualitative analysis revealed essential themes, such as the importance of English, lecturer support, and challenges in learning. This study's conclusion shows that students' English learning motivation is influenced by intrinsic and extrinsic factors and the importance of support in overcoming learning challenges. This study provides insights for developing more effective English learning strategies in academic environments.